2018
DOI: 10.1177/1940161218782397
|View full text |Cite
|
Sign up to set email alerts
|

Reporting in Latin America: Issues and Perspectives on Investigative Journalism in the Region

Abstract: This study investigates challenges faced by investigative journalists in Latin America, one of the most dangerous places in the world for reporters. Guided by the hierarchy of influences model, we analyzed answers from 1,543 journalists, journalism educators, and journalism students in the region. We identified both single and multilevel constraints impeding investigative reporting in Latin America. Single-level influences are those that are better analyzed by focusing on one level of the hierarchical model. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 20 publications
0
18
0
4
Order By: Relevance
“…Gonz alez de Bustamante and found that Mexican reporters have to deal with intimidation and unthinkable crimes committed against them by criminal groups or corrupt government officials. Similarly, Saldaña and Mourão (2018) found investigative journalism is scarce in Mexico precisely because of the violence and organized crime constantly threatening those interested in conducting investigative reporting. The latest reports on violence against the press indicate that half of the journalists killed in 2019 were from Mexico, making this country the second deadliest country for journalists, only after Syria (Beiser 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gonz alez de Bustamante and found that Mexican reporters have to deal with intimidation and unthinkable crimes committed against them by criminal groups or corrupt government officials. Similarly, Saldaña and Mourão (2018) found investigative journalism is scarce in Mexico precisely because of the violence and organized crime constantly threatening those interested in conducting investigative reporting. The latest reports on violence against the press indicate that half of the journalists killed in 2019 were from Mexico, making this country the second deadliest country for journalists, only after Syria (Beiser 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The new millennium has also brought new challenges for investigative journalism in the region. Saldaña and Mourão (2018), in their study of the main challenges faced by Latin American investigative journalists, found that crime and corruption were the most common constraints identified by reporters. Crime and corruption were mentioned by reporters of 17 out of 18 countries in the sample.…”
Section: Investigative and Watchdog Journalism In Latin Americamentioning
confidence: 99%
See 1 more Smart Citation
“…La investigación incorpora entidades de España y América Latina. Los sistemas mediáticos de estas regiones se han caracterizado tradicionalmente por presentar problemas y retos compartidos, entre los que cabe destacar: la limitada autonomía periodística, las dificultades de acceso a datos públicos, la alta concentración de medios de comunicación, el alto nivel de polarización de la esfera pública y la influencia de la clase política sobre el periodismo (Baumgartner y Bonafont, 2015;Hallin y Papathanassopoulos, 2002;Masip, Ruiz y Suau, 2018;Reporteros Sin Fronteras, 2020;Saldaña y Mourão, 2018). La preocupación por el creciente avance de la desinformación también permea los contextos español y latinoamericano.…”
Section: Objetivos Y Metodologíaunclassified
“…Over the past 10 years, the number of non-profit investigative news organizations in Latin America has experienced important growth and enjoyed increasing success (Salaverría et al, 2019). This proliferation of non-profit investigative journalism institutions is due, in part, to a remarkable effort made by their respective governments and institutions to return to democracy over the past 20 years (Saldaña & Mourão, 2018); also, to greater availability of international funds to sustain research initiatives and finally, to intelligent management developed by their founders, most of them expert and experienced professionals, whose capability in the fight against corruption continues to guide them in the arduous task of making their way into the Latin American public space and consolidating their position within those democracies.…”
Section: Introductionmentioning
confidence: 99%